Polarity-Dependent Modulation of Multi-Spectral Neuronal Activity by Transcranial Direct Current Stimulation - Wiesman, Alex I. (Cortex, 2018)
The ability to preferentially deploy neural resources to the visual space is an important component of normative cognitive function, however, the population-level cortical dynamics that sub-serve this ability are not fully understood. Specifically, rhythmic activity in the occipital cortices (e.g., theta, alpha, and gamma oscillations) has been strongly implicated in this cognitive process, but these neural responses are difficult to non-invasively manipulate in a systematic manner. In this study, transcranial direct-current stimulation (tDCS) was used to modulate brain activity, while high-density magnetoencephalography (MEG) was employed to quantify changes in rhythm-specific neural activity in the occipital cortices of 57 adults performing a visuospatial processing paradigm. All MEG data was analyzed using advanced source reconstruction and oscillatory analysis methods. Our results indicated that basal levels of occipital alpha activity were increased by an occipital-anodal/supraorbital-cathodal tDCS montage, while basal gamma levels in the same cortices were decreased by tDCS using the same montage with its polarity reversed (occipital-cathodal/supraorbital-anodal). In other words, stimulation with the occipital-anodal montage increased local spontaneous alpha (10–16 Hz) activity, while stimulation with the occipital-cathodal montage selectively decreased local gamma (64–90 Hz) activity. Neither polarity affected stimulus-induced oscillations in the alpha or gamma range. Additionally, these modulations strongly predicted the subsequent formation of fronto-visual functional connectivity within distinct oscillatory rhythms, as well as behavior on the visuospatial discrimination task. These findings provide insight into the multifaceted effects of tDCS on cortical activity, as well as the dynamic oscillatory coding of salient information in the human brain.